2006
DOI: 10.1371/journal.pone.0000083
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia and Mortality after Coronary Artery Bypass Grafting

Abstract: BackgroundThe independent prognostic impact, as well as the possible causal role, of hyperhomocysteinemia (HHcy) in coronary artery disease (CAD) is controversial. No previous study specifically has addressed the relationship between HHcy and mortality after coronary artery bypass grafting (CABG) surgery. The aim of this study is to evaluate the prognostic impact of HHcy after CABG surgery.Methodology and Principal FindingsWe prospectively followed 350 patients who underwent elective CABG between May 1996 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Contrary to Rodionov’s ( 28 ) observation that Hcy is only a bystander in CAD, our results support the opinion that Hcy plays an active role in SVG progression. Girelli et al ( 29 ) observed similar results in 350 CAD patients after a mean follow-up of 4.8 years; Hcy was an important and independent prognostic factor of mortality after CABG. Furthermore, fasting Hcy level correlated positively with CRP.…”
Section: Discussionmentioning
confidence: 60%
“…Contrary to Rodionov’s ( 28 ) observation that Hcy is only a bystander in CAD, our results support the opinion that Hcy plays an active role in SVG progression. Girelli et al ( 29 ) observed similar results in 350 CAD patients after a mean follow-up of 4.8 years; Hcy was an important and independent prognostic factor of mortality after CABG. Furthermore, fasting Hcy level correlated positively with CRP.…”
Section: Discussionmentioning
confidence: 60%
“…Methylcytosine-enriched samples were then fluorescently labeled (Cy5), and input control samples (not methylcytosine-enriched) were fluorescently labeled (Cy3), followed by competitive hybridization to a high throughput 3ϫ750k NimbleGen array containing CpG islands and all annotated gene promoters in the human genome. Signals were detected with the NimbleGen microarray scanner MS 200 (16). The Comprehensive High-throughput Array for Relative Methylation (CHARM) method in R Studio previously described (3) was modified to analyze the meDIP DNA methylation arrays for control and 500 mol/l SAMtreated cells (3,27).…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, many studies demonstrate a clear association between HHcy and coronary artery disease, atherosclerosis, hypertension and neurodegenerative diseases [131] . Indeed, HHcy can be considered as a predictive biomarker of cardiovascular mortality in patients affected by coronary artery disease, and plasma levels of Hcy correlate with the severity of atherosclerosis [132] .…”
Section: Hydrogen Sulfide and Hyperhomocysteinemia-related Endotheliamentioning
confidence: 99%